Work Discipline and Work Motivation on Employee Performance - Muhammad Irfan Nasution; Nirwana Priangkatara (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
This study aims to determine partially and simultaneously the effect of work discipline and work motivation on employee performance at office Kantor Badan Pengelolaan Keuangan dan Aset Daerah Kabupaten Langkat. The population used in this study amounted to 50 employees. While the sample taken is 50 employees, the sampling technique used is total sampling. This study uses a type of quantitative research. The research results indicate that work discipline has a significant influence on employee performance. Work motivation has a significant effect on employee performance compliance. Then together, work discipline and work motivation have a moderate influence on employee performance